2014
DOI: 10.1002/2013jd021031
|View full text |Cite
|
Sign up to set email alerts
|

Radar observations of MJO and Kelvin wave interactions during DYNAMO/CINDY2011/AMIE

Abstract: Radar and sounding data collected during the Dynamics of the Madden-Julian Oscillation (DYNAMO), the Cooperative Indian Ocean Experiment on Intraseasonal Variability in the Year 2011 (CINDY2011), and the Atmospheric Radiation Measurement (ARM) Madden-Julian Oscillation Investigation Experiment (AMIE) field campaigns in the equatorial Indian Ocean to study the initiation of the Madden-Julian Oscillation (MJO) are used to examine the precipitation, cloud, and moisture characteristics during the MJO and convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Additional details of how the SMART‐R rainfall product was produced are given in DePasquale et al . []. The estimated uncertainty in 3 h domain‐averaged SMART‐R rainfall increases with rain rate but is generally <10% (Weixin Xu 2016, personal communication).…”
Section: Data and Proceduresmentioning
confidence: 99%
“…Additional details of how the SMART‐R rainfall product was produced are given in DePasquale et al . []. The estimated uncertainty in 3 h domain‐averaged SMART‐R rainfall increases with rain rate but is generally <10% (Weixin Xu 2016, personal communication).…”
Section: Data and Proceduresmentioning
confidence: 99%
“…During the DYNAMO field campaign [ Yoneyama et al , ] three MJO events were intensively studied [ DePasquale et al , ; Gottschalck et al , ; Johnson and Ciesielski , ; Kent et al , ]. The November 2011 MJO was associated with two sequential atmospheric Kelvin waves.…”
Section: The Dynamo Field Project: Case Study Of Sequential Cckwsmentioning
confidence: 99%
“…Nine of these events were associated with the active phase of the MJO, while seven developed during the suppressed phase [ Gottschalck et al , ]. Radar observations were used to analyze the difference in structure and intensity of the CCKWs during the suppressed and active phases of the MJO in DYNAMO [ DePasquale et al , ]. In the active phase, the waves were more intense with higher moisture and more clouds, possibly impacting the radiative effects of the wave.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of high-frequency disturbances utilizing the CINDY2011/DYNAMO field observation data have been undertaken (e.g., JC13; Zuluaga and Houze 2013;DePasquale et al 2014). By analyzing radar data, DePasquale et al (2014) discussed the roles of convectively coupled Kelvin waves in deep moistening during the developing phase of the MJO events. JC13 reported that westward-moving 2-day disturbances were pronounced in MJO1, whereas 4-5-day disturbances were more frequent in MJO2.…”
Section: B Roles Of High-frequency Disturbancesmentioning
confidence: 99%